The role of air defense missile units in the air space control and protection - Gordić Miodrag; Petrović Ivan; Cvetković Krum (Војно дело, 2014)
Any use of modernly equipped and armed aircraft brings a dialectical need to develop ways of adequate countering and of the protection of own defense forces, in order to establish a balance and a new quality in the content of the armed struggle. Keeping the above in mind, as well as the changes made in the area of politics and economy, both globally and locally, as well as their impact on the security of the less developed and influential states and their natural and social resources, and the increased risk of the occurrence of asymmetric threats from the airspace, the conditions have been created to review the place and role of air defense missile units in the execution of their missions - the role and tasks of not only the Air Force and Air Defense, but the armed forces as a whole. The fact that the air defense missile units have a preventive role through the execution of tasks in the airspace control and protection, it follows that they are an important factor in the country's defense. Also, the experiences of armed conflicts carried out over the past decades clearly suggest that the incapability of air defense, with the air defense missile units as its striking component, to successfully counter the attacks from the air, unconditionally leads to a rapid defeat of the armed forces as a whole This paper consists of two parts. The first part contains a conceptual definition of air defense system, while the second part explains in detail the way to achieve a preventive role of air defense missile units executing the tasks of the airspace control and protection.